Heteroactivism, Homonationalism and National Projects - Boulila, Stefanie C.; Browne, Kath (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
Oppositions and reactions to contestations of the hetero-patriarchal order are becoming a main site of engagement for feminist and queer activism and scholarship. Yet further spatial and intersectional attention to these oppositions, dubbed “anti-gender politics”, is needed to move beyond single-issue analyses of their geographical ‘placings’. This special issue seeks to develop geographical analyses of such contestations by situating them within nationalisms and racial politics. The papers in this special issue develop the concept of heteroactivism to deliver conceptual and empirical insights into the spatialities of oppositions and resistances against gender and sexual equalities that are manifest as part of broader racial and national projects.